Dampak Pertumbuhan Sektor Pariwisata dan Perikanan Terhadap Produk Domestik Regional Bruto (PDRB) Menurut Lapangan Usaha: Bukti Empiris dari Kabupaten Wakatobi, Indonesia - Rizal Rizal; Wahyu Muh Syata; Harjun Harjun; Ilhamurraman M Hubaib (Indonesia Economic Journal, 2026)
This study aims to empirically analyze the impact of the growth of the tourism sector (represented by the Accommodation and Food and Beverage subsector) and the fisheries sector on the Total Gross Regional Domestic Product (GRDP) Growth in Wakatobi Regency, Indonesia, during the 2015–2019 period. As an archipelagic region that relies on these two sea-based sectors, identifying their contributions and interactions is crucial for sustainable economic development. Using a time series approach with Multiple Linear Regression Analysis, secondary data of GRDP at Constant Prices (ADHK) 2010 from BPS Wakatobi Regency was processed. The estimation results show that the model has very high explanatory power (R^2 = 0.883), which indicates that 88.3% of the variation in Total GRDP is influenced by both variables. However, the results of the Simultaneous Significance Test (F Test) (Prob. 0.116) and Partial Test (t Test) found that neither Tourism nor Fisheries Sector Growth statistically had a significant effect on Total GRDP Growth. Synergy analysis through the interaction model also did not prove significant. These findings indicate that Wakatobi Regency's total GRDP growth is currently dominated by non-basic factors, represented by model constants (such as government spending and household consumption), while leakage and weak inter-sectoral linkages prevent the significant impact of basic sectors from being internalized into aggregate GRDP. This study recommends the need for policies to strengthen backward linkages between the tourism sector and local products and further analysis of disaggregated GRDP by industry to identify true spillover effects.